Prevalence and Risk Factors of Hypertension in Type 2 Diabetics in Benin. - AMOUSSOU-GUENOU, KOFFI DANIEL; wanvoegb, FINANGNON ARMAND; AGBODANDE, KOUESSI ANTHELME; DANSOU, ALIHONOU; TCHABI, YESSOUFOU; EYISSE, YASMINE; AMOUSSOU-GUENOU FANDI, ARNAULDE; MOUSSE, LATIF (My University, 2015)
Background: Couple High Blood Pressure (HBP)-Diabetes is a morbid association and a public health problem. The aim of this study was to determine the actual epidemiological profile of HBP in type 2 diabetic. Methods: A cross-sectional, prospective, descriptive and analytical study was conducted at Banque d’insuline of Cotonou, Polyclinique Atinkanmey and CHUD-Ouémé-Plateau. The study took place over a period of 06 months from March 01 to August 30, 2014. The study included patients with type 2 diabetes mellitus seen at consultation who agreed to participate in the study. Results: The survey involved 400 individuals. Among them, 34% were male and the sex ratio was 0.48. The mean age was 55.6 ± 10.3 years (range 28 - 87 years). The prevalence of hypertension in type 2 diabetic patients was 70%. The risk factors significantly associated with HBP were age above 55 years (p = 0.000), abdominal obesity (p = 0.036), a diabetes duration above 10 years (p = 0.009). Complications significantly associated with HBP were stroke (p = 0.013) and diabetic foot (p = 0.044). Conclusion: HBP-type 2 Diabetes association is frequent in Benin.
Keywords: Diabetes; Prevalence; Risk Factors; Benin